BUSINESS ETHICS FORMULATION BASED ON LEGAL ASPECTS IN THE IMPLEMENTATION OF GCG (GOOD CORPORATE GOVERNANCE) - Putri, Mitrida Iga Rahma; Turisno, Bambang Eko (Tadulako University, 2020)
Corporate governance is defined as a subject that has many aspects. One of the main topics in corporate governance concerns issues of accountability and mandate responsibility, specifically the implementation of guidelines and mechanisms to ensure good behavior and protect the interests of shareholders. Weak corporate governance is often cited as one of the causes of financial crises in Asian countries. The main characteristic of weak corporate governance is selfish action on the part of company managers. The method used is a normative juridical method with the types and techniques of data collection with legal literature and literature review. This study aims to find out and get a picture of the concept of good corporate governance in business ethics and to know the formulation of business ethics based on legal aspects in the application of corporate governance in creating good corporate performance. Good corporate governance can be created if there is a balance of interests between all parties concerned with our business. Identifying the balance in its existence requires a measurement system that can absorb every strategic and operational dimension of the business.